Effect of vitamin D supplementation on cardiac-metabolic risk factors in elderly: a systematic review and meta-analysis of clinical trials - Appannah, Geeta; Djalainia, Shirin; Pourrostami, Kumars; Naderali, Ebrahim Khalil; Khazdouz, Maryam; Qorbani, Mostafa (BioMed Central, 2022)
Background: There has been a longstanding interest in the potential effect of vitamin D in preventing cardiac-metabolic diseases. However, there are divergent results regarding the impact of vitamin D supplementation (VDS) on managing cardiac-metabolic outcomes in the elderly population. Material and method: We systematically searched electronic databases; Web of Science, PubMed, Scopus, EMBASE, Cochrane, and ProQuest. We included all trials that evaluated the effect of VDS on cardiac-metabolic risk factors in the elderly population, which were published until 30 September 2021. The effects of VDS on cardiac-metabolic outcomes were assessed using standardized mean difference (SMD). A random-effect model was used to pool the SMD and 95% confidence interval (CI). Result: The literature search identified 4409 studies, of which 12 trials met inclusion criteria. Results of random effect meta-analysis indicated a significant reduction in total cholesterol (TC) (SMD: − 0.14 mg/dl; 95% CI: − 0.25, − 0.02) and triglyceride (TG) (SMD: − 0.45 mg/dl; 95% CI: − 0.86, − 0.04) with VDS compared to the placebo. The subgroup analyses revealed that the reduction of TG in patients with diabetes and vitamin D deficiency was significant. Furthermore, short-term intervention (≤ 6 months) induced a significantly lower level of TG and insulin in comparison to longer duration (> 6 months). Conclusion: The study suggests that VDS could improve insulin concentration and dyslipidemia in the elderly population. The systematic review was registered in Alborz university of medical sciences with 2060-01-03-1397 number and the Ethics council IR.ABZUMS.REC.1397.207 number.